Systematic analysis of enoxaparins from different sources with online one- and two-dimensional chromatography. Issue 12 (24th April 2019) - Ouyang, Yilan; Zhu, Meng; Wang, Xin; Yi, Lin; Fareed, Jawed; Linhardt, Robert J.; Zhang, Zhenqing
Abstract : Enoxaparin, one of the most important low-molecular-weight heparins (LMWHs), is widely used as a clinical anticoagulant. Abstract : Enoxaparin, one of the most important low-molecular-weight heparins (LMWHs), is widely used as a clinical anticoagulant. Different production processes and animal sources of its precursor (unfractionated heparin) can result in the structural diversity of enoxaparin. In this study, 38 lots of enoxaparin prepared at different times, from different providers and animal sources, were systematically analyzed. SEC and SAX were used to analyze the oligosaccharide dispersity and structural compositions (disaccharide domains) of enoxaparins by size and charge, respectively. The results provide clues as to whether the structural variations in enoxaparin, observed in oligosaccharide mapping and/or disaccharide analysis, are attributable to differences in the animal sources of its heparin precursor or enoxaparin production processes based on times or brands. The representative enoxaparins were fingerprinted with online multiple heart-cut two-dimensional liquid chromatography-mass spectrometry (MHC-2DLC-MS). The profiles in MHC-2DLC-MS showed the detailed structural information of enoxaparins. In addition, the binding capacities to antithrombin III (AT) of these 38 lots of enoxaparins were detected using surface plasmon resonance (SPR) with the competitive inhibition mode. The results showed that the glycan size distribution of an enoxaparin is more related to its production process. The disaccharide composition, sequence and the variety of glycans of an enoxaparin are more related to its AT binding-based anticoagulant activity.